2022
DOI: 10.3389/fpubh.2022.1046223
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of longitudinal changes in four surrogate insulin resistance indexes for incident T2DM in middle-aged and elderly Chinese

Abstract: AimsPrevious studies suggested a significant relationship between four surrogate indexes of insulin resistance and subsequent type 2 diabetes mellitus (T2DM). But the association of longitudinal changes (denoted as -D) in CVAI (Chinese visceral adiposity index), LAP (lipid accumulation product), TyG (triglyceride-glucose), and TG/HDL-C (triglyceride/ high-density lipoprotein cholesterol) indexes with the risk of T2DM remained uncertain. We aimed to compare the changes in those four surrogate indexes for predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The mechanism of diabetic patients with IR is often attributed to glucose toxicity and lipotoxicity ( 25 ). Some studies found that long-term monitoring of TyG index changes was valuable for the early identification of individuals at high risk of diabetes ( 26 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of diabetic patients with IR is often attributed to glucose toxicity and lipotoxicity ( 25 ). Some studies found that long-term monitoring of TyG index changes was valuable for the early identification of individuals at high risk of diabetes ( 26 , 27 ).…”
Section: Discussionmentioning
confidence: 99%